Soybean Cost-Return Budget in North Central Kansas - Dhuyvetter, Kevin C. (My University, 1999)
This publication provides estimated cost and returns for forward farm planning for soybeans in north central Kansas.
MF2160_1999_10
Keywords: MF2160; Crops; Economics; MF